QUEER FEMINITY MULTIMODAL DISCOURSE ANALYSIS ON WEB SERIES BOUNDARIES: CONFINING OR FREEING(?) - Samuel Rihi Hadi Utomo; Wening Udasmoro (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2021)
This study attempts to explain and dissect the position of queer femininity in the gender order constellation in the context of queer in Indonesia, exploring the position of queer femininity on the Batas web series. Analysis of multimodal discourse from the perspective of Kress and van Leeuwen with terminologies; representational meaning, interactive meaning and compositional meaning, shows that queer femininity discourse within Batas explains the shifting and blurring of boundaries between subject-object and active-passive which always refers to rigid masculine and feminine binary. Queer femininity discourse in Batas shows that femininity is not monolithic. A queer perspective can provide a subversive position, negotiate and resist the dominant discourse. On the other hand, it shows the idealized codes of heterosexual discourse, patriarchy and media. Keywords: Queer, Femininity, Discourse, Multimodal, Webseries